Interventional treatment of endobronchial hamartomas and lipomas - Özgül, Mehmet Akif; Çetinkaya, Erdogan; Gül, Şule; Dinçer, Huseyin Erhan; Acat, Murat; Boyacı, Hilal; Özgül, Güler (European Journal of Oncology and Environmental Health, 2016)
Objective: Endobronchial benign tumors are rarely seen in lung cancers or in pulmonary benign tumors. In recent years, endoscopic treatment has increasingly been used to treat benign endobronchial lesions. Methods: Data from all adult patients diagnosed with a histologically proven endobronchial hamartoma and lipoma were collected between 2009 and 2014 at our clinic in the Yedikule Chest Diseases Education and Research Hospital. Results: 9 patients were included in the study; 6 patients were diagnosed with endobronchial hamartoma(66%) and 3 had endobronchial lipoma. Six patients were symptomatic. All patients underwent rigid bronchoscopy and biopsies taken during treatment were diagnostic in all cases. Lesions were mostly located at the lobar bronchus. Seven (77%) cases were successfully treated and there were no complications because of the procedure. Two patients was sent for lobectomy because of inadequate debulking. Recurrence was not seen in any patient. Conclusion: Interventional bronchoscopic techniques may be a safe and effective method for diagnosing and treating endobronchial benign tumors.